2018
DOI: 10.4254/wjh.v10.i10.731
|View full text |Cite
|
Sign up to set email alerts
|

Spleen stiffness mirrors changes in portal hypertension after successful interferon-free therapy in chronic-hepatitis C virus patients

Abstract: AIMTo investigate changes in spleen stiffness measurements (SSMs) and other non-invasive tests (NITs) after treatment with direct-acting antivirals (DAAs) and identify predictors of SSM change after sustained virological response (SVR).METHODSWe retrospectively analysed 146 advanced-chronic liver disease (ACLD) patients treated with DAA with available paired SSM at baseline and SVR24. Liver stiffness (LSM), spleen diameter (SD), platelet count (PLT) and liver stiffness-spleen diameter to platelet ratio score(L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…In contrast to LSM by VCTE or other methods, SSM may mirror portal hypertension without being directly influenced by the resolution of hepatic inflammation. 117,118,123,124 However, data after etiological cure are lacking. Finally, MR-based techniques seem to be sensitive for SVR-induced changes and have shown to be prognostic for hepatic decompensation after SVR; however, they have yet to be correlated with HVPG.…”
Section: Monitoring the Evolution Of Portal Hypertension And Predictimentioning
confidence: 99%
“…In contrast to LSM by VCTE or other methods, SSM may mirror portal hypertension without being directly influenced by the resolution of hepatic inflammation. 117,118,123,124 However, data after etiological cure are lacking. Finally, MR-based techniques seem to be sensitive for SVR-induced changes and have shown to be prognostic for hepatic decompensation after SVR; however, they have yet to be correlated with HVPG.…”
Section: Monitoring the Evolution Of Portal Hypertension And Predictimentioning
confidence: 99%
“…This is a retrospective cohort study of patients with HCV-related ACLD, defined by LSM >10 kPa at baseline, 13 who were successfully treated with DAAs in our centre between 2015 and 2017 and had available valid measurements of LSM and SSM before and 6 months (SVR24) after antiviral treatment. 14,15 These patients have been included in a previous study evaluating the role of non-invasive tests in predicting decompensation after SVR achievement 15 ; however, the relationship between elastography and HCC development was not previously explored.…”
Section: Study Participants and Follow-upmentioning
confidence: 99%
“…Conversely, ELF showed good accuracy for CSPH, but was not associated with fibrosis regression Liver stiffness and VITRO score [ 43 ] In this cohort of DAA-treated HCV patients, TE and VITRO score performed well in ruling in/out CSPH after SVR. Their accuracy was especially high if used in a sequential manner, leaving 25% of patients unclassifiable Spleen stiffness [ 137 ] In this cohort of DAA-treated HCV patients, SS decreased significantly after SVR, more so in patients without BL CSPH. However, the presence and grade of PP was estimated based on LS, and no direct HVPG measurements were performed Spleen stiffness [ 138 ] This proof-of-concept study demonstrated that a decrease in spleen stiffness accurately predicts the hemodynamic response to primary prophylaxis with NSBB (Carvedilol) in patients with HREV.…”
Section: Biomarkers Of Ph Regressionmentioning
confidence: 99%